Comparative analysis of the complete mitogenome of Geoffroea decorticans: a native tree surviving in the Atacama Desert - Contreras-Díaz, Roberto; Carevic, Felipe S.; van den Brink, Liesbeth (Frontiers in Genetics, 2023)
Chañar (Geoffroea decorticans (Gill., ex Hook. & Arn.) Burkart) has been highly significant for indigenous people in the Atacama Desert for over 3,000 years. Through evolutionary processes, the G. decorticans mitogenome likely underwent changes facilitating its adaptation to the extreme conditions of the Atacama Desert. Here, we compare the mitochondrial genome of G. decorticans with those of other Papilionoideae family species. The complete mitogenome of G. decorticans was sequenced and assembled, making it the first in the genus Geoffroea. The mitogenome contained 383,963 base pairs, consisting of 33 protein coding genes, 21 transfer RNA genes, and 3 ribosomal RNA genes. The Chañar mitogenome is relatively compact, and has two intact genes (sdh4 and nad1) which were not observed in most other species. Additionally, Chañar possessed the highest amount of mitochondrial DNA of plastid origin among angiosperm species. The phylogenetic analysis of the mitogenomes of Chañar and 12 other taxa displayed a high level of consistency in taxonomic classification, when compared to those of the plastid genome. Atp8 was subjected to positive selection, while the ccmFc and rps1 were subjected to neutral selection. This study provides valuable information regarding its ability to survive the extreme environmental conditions of the Atacama Desert.